2020
DOI: 10.5114/pjp.2020.103709
|View full text |Cite
|
Sign up to set email alerts
|

Grading placental fetal vascular malperfusion and short-term perinatal outcome

Abstract: This retrospective analysis was performed to seek possible associations of the global fetal vascular malperfusion (GFVM) and grade of segmental fetal vascular malperfusion (SFVM) with early perinatal outcome. Clinical associations of 538 consecutive cases of placental fetal vascular malperfusion (FVM), including 374 cases of SFVM (group 1: 308 low-grade, group 2: 66 high-grade), and 65 cases of GFVM without segmental villous changes (group 3), were statistically compared. Histological SFVM was graded on HE (Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 34 publications
(84 reference statements)
0
9
0
Order By: Relevance
“…In postnatal complications, FVM seems to be a less sensitive tool for the prediction of complications [38]. The NICU stay in the infants analysed here was around 70% in all groups (Table I), but high-grade distal FVM is associated with complicated short-term perinatal outcome, no matter if remote or recent [3]. CD34 immunohistochemistry and/or mineralization histochemistry diagnosed/upgraded to high-grade FVM has the same short-term prog-nostic significance as high-grade segmental FVM diagnosed by H&E only [3], but not global FVM, which was also confirmed by this analysis (Table II).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…In postnatal complications, FVM seems to be a less sensitive tool for the prediction of complications [38]. The NICU stay in the infants analysed here was around 70% in all groups (Table I), but high-grade distal FVM is associated with complicated short-term perinatal outcome, no matter if remote or recent [3]. CD34 immunohistochemistry and/or mineralization histochemistry diagnosed/upgraded to high-grade FVM has the same short-term prog-nostic significance as high-grade segmental FVM diagnosed by H&E only [3], but not global FVM, which was also confirmed by this analysis (Table II).…”
Section: Discussionmentioning
confidence: 82%
“…In the latter application, the immunostaining increased the sensitivity of placental FVM diagnosis in stillbirth, was capable of upgrading low-grade FVM to high grade by increasing the number of involved distal chorionic villi (not seen on H&E staining) [11], and of disclosing temporal heterogeneity of FVM lesions by adding more recent lesions with clustered endothelial fragmentation (2 days) to other established lesions of FVM: clustered stromal vascular karyorrhexis (3 days), clusters of hypovascular distal villi (several days), clusters of sclerotic chorionic villi (2 weeks), or mineralized chorionic villi (> 2 weeks) [12,13]. We also showed that distal villous lesions of FVM are clinically more relevant than proximal large-vessel FVM lesions [14] and that high-grade FVM is associated with adverse short-term perinatal outcome whether diagnosed by H&E, immunohistochemistry, or histochemistry staining [3].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…The cases identified using immunohistochemistry showed less abnormal clinical and placental phenotypes that those identified using hematoxilin‐eosin staining alone, likely because the former had a duration that was shorter than that required to bediagnosable using hematoxilin‐eosin staining. Previously we proved that high‐grade segmental FVM diagnosed by or upgraded by CD34 immunostain portends the same poor outcome for the fetus as when diagnosed using hematoxilin‐eosin staining 34 . Therefore, the CD34 immunostaining may be either diagnostic or contributory in explaining the cause of the otherwise inexplicable stillbirths without high‐grade FVM according to hematoxilin‐eosin staining alone.…”
Section: Discussionmentioning
confidence: 96%
“…Previously we proved that high-grade segmental FVM diagnosed by or upgraded by CD34 immunostain portends the same poor outcome for the fetus as when diagnosed using hematoxilin-eosin staining. 34 Therefore, the CD34 immunostaining may be either diagnostic or contributory in explaining the cause of the otherwise inexplicable stillbirths without high-grade FVM according to hematoxilin-eosin staining alone.…”
Section: Discussionmentioning
confidence: 99%